1984
DOI: 10.1068/p130075
|View full text |Cite
|
Sign up to set email alerts
|

Stroop Interference Based on the Synaesthetic Qualities of Auditory Pitch

Abstract: The equivalence of perceptual experience across the sensory modalities, most vividly observed in synaesthetes, is rarely discussed in contemporary cognitive psychology. It is suggested, however, that the concepts and paradigms of human information processing are ideally suited to test, for example, the fundamental assumption that the synaesthetic qualities of a stimulus are rapidly and automatically encoded. In a preliminary experiment subjects were asked to rate each of four auditory tones on a series of 7-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
101
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 19 publications
11
101
0
Order By: Relevance
“…We measure Stroop congruity both in filtering and at baseline,' which is defined as a difference in classification reaction time (RT) between trials in which the color and the word correspond (i.e., congruent trials) and trials in which the color and the word conflict (i.e., incongruent trials). Congruity measures have frequently substituted for Stroop's original measure (see, e.g., Nealis, 1973;Schulz, 1979;Sichel & Chandler, 1969;Simon & Berbaum, 1990;Simon & Sudalaimuthu, 1979; G. J. W. Smith, 1970) and have been used in tests of many other dimensions whose values have a correspondence quality (e.g., Clark & Brownell, 1976;Melara, 1989;Redding & Tharp, 1981;Walker & S. Smith, 1984).…”
Section: Stroop and Garner Effectsmentioning
confidence: 99%
“…We measure Stroop congruity both in filtering and at baseline,' which is defined as a difference in classification reaction time (RT) between trials in which the color and the word correspond (i.e., congruent trials) and trials in which the color and the word conflict (i.e., incongruent trials). Congruity measures have frequently substituted for Stroop's original measure (see, e.g., Nealis, 1973;Schulz, 1979;Sichel & Chandler, 1969;Simon & Berbaum, 1990;Simon & Sudalaimuthu, 1979; G. J. W. Smith, 1970) and have been used in tests of many other dimensions whose values have a correspondence quality (e.g., Clark & Brownell, 1976;Melara, 1989;Redding & Tharp, 1981;Walker & S. Smith, 1984).…”
Section: Stroop and Garner Effectsmentioning
confidence: 99%
“…As part of their commitment to the notion that elementary stimulus features have connotative meanings, Karwoski et al (1942) proposed an early precursor of more recent claims that cross-sensory correspondences can reflect the semantic coding of such features (e.g., Martino & Marks, 1999;Walker & Smith, 1984). Karwoski et al suggested that cross-sensory correspondences arise from extensive crossactivation between corresponding places on dimensions of connotative meaning that are aligned with each other.…”
mentioning
confidence: 99%
“…For example, people classifying simple visual stimuli according to their brightness or angularity respond more easily when a concurrent auditory tone has corresponding pitch (i.e., high for bright and angular, low for dark and curved) than when it does not have corresponding pitch (i.e., low for bright and angular, high for dark and curved) (Marks, 1987). Because pitch is incidental to the requirements of the task in this situation, registration of its cross-sensory connotations of brightness and angularity is thought to be automatic (see, e.g., Walker & Smith, 1984).…”
mentioning
confidence: 99%
See 2 more Smart Citations